Robust mucosal-homing antibody-secreting B cell responses induced by intramuscular administration of adjuvanted bivalent human norovirus-like particle vaccine. Issue 4 (15th January 2015) - Sundararajan, Aarthi; Sangster, Mark Y.; Frey, Sharon; Atmar, Robert L.; Chen, Wilbur H.; Ferreira, Jennifer; Bargatze, Robert; Mendelman, Paul M.; Treanor, John J.; Topham, David J.
Highlights GI.1/GII.4 bivalent Norovirus-like particle vaccine elicited B cell plasmablasts in peripheral blood. High frequencies of VLP-specific antibody secreting cells were present in peripheral blood. Plasmablasts exhibited a strongly mucosal homing phenotype and high proportions of IgA secreting cells. Results are consistent with recall of pre-existing cellular immune memory.